A systematic review of interventions embedded in curriculum to improve university student wellbeing. (November 2022) - Upsher, Rebecca; Nobili, Anna; Hughes, Gareth; Byrom, Nicola
Abstract: Background: As concerns around student mental health increase, universities are looking at preventative and universal interventions. The aim was to conduct a systematic review of curriculum-embedded interventions that target student mental health and wellbeing at university. Method: This was a systematic review of longitudinal pre-/post-studies of curriculum-embedded interventions to improve the mental health and wellbeing of students. Seven electronic databases were searched from June 2015 to May 2020. The vote counting method was used to synthesise studies. Results: Forty-six studies were included in the review. Studies were heterogeneous, and mostly underpowered and rated 'poor' in the risk of bias assessment due to poor and inconsistent reporting. Overall, most curriculum-embedded interventions did not influence stress or anxiety. Discussion: There is no strong evidence to support the impact of curriculum-embedded interventions for improving student mental health or wellbeing. Greater funding opportunities would allow for multi-programme and inter-institutional collaboration to improve the power of studies. Improved quality of reporting would enable high-quality meta-analyses, optimizing conclusions being drawn. Highlights: Evidence to support student wellbeing curriculum-embedded interventions is limited. Many studies were rated poor risk of bias due to inconsistent reporting. Consistency of wellbeing outcomes could improve synthesis.